PENGARUH PELATIHAN DAN KOMPENSASI TERHADAP MOTIVASI KERJA KARYAWAN DI DIVISI FINISHING CV. LAKSANA - Gilang Christian Elvin; Ari Pradhanawati (Universitas Diponegoro, 2019)
CV. Laksana as a large company engaged in autobody manufacture still have an employees with a low work motivation such as production target that aren’t finished on time, the quality of production isn’t in accordance with company standards, etc. This can be caused by a lack of ability of employees because they lack of training or compensation given by the company isn’t good enough. The purpose of this research are to acknowledge the impact of training and compensation towards the work motivation of CV. Laksana employees. This research are using explanatory research and collecting data methods using interview and questionnaires as data collection tools with a sample of 72 respondents of CV. Laksana employees which is accussed by probability sampling methods and random sampling methods. The analyzing methods used in this research validity test, reliability test, coefficient correlation, regression test, determination coefficient, t and F signification test using SPSS 25.0 application. The result of this research shows that training variables had an impact 61.7% towards work motivation, at the other hand compensation varieble had an impact 70.8% towards work motivation, and simultaneously training and compensation have influenced on work motivation 71.6%. This means the better training and compensation given by the company the better work motivation of the employees to finish their job. This research shows that compensation variable have more impact towards work motivation rather than training variable. It is suggested to the company management to keep maintain or even improve the quality of training and keep evaluating about the compensation given to keep maintain the work motivation of the employees.